Lymphocyte Immunophenotyping and CD4/CD8 Ratio in Cerebrospinal Fluid for the Diagnosis of Sarcoidosis-related Uveitis. (17th February 2021) - Paule, Romain; Denis, Laure; Chapuis, Nicolas; Rohmer, Julien; Hadjadj, Jérôme; London, Jonathan; Chauvin, Anthony; Bonnet, Clémence; Mouthon, Luc; Le Jeunne, Claire; Monnet, Dominique; Blanche, Philippe; et al.
ABSTRACT: Background : This study aimed to assess the diagnostic relevance of CD4/CD8 ratio in cerebrospinal fluid (CSF) for the etiological diagnosis work-up of uveitis. Methods : We consecutively included patients who were referred to our department for the diagnostic workup of intermediate and/or posterior uveitis. Etiological diagnoses were established in a blind manner regarding CD4/CD8 ratio. Results : Fifty-two patients were included. A diagnosis of ocular sarcoidosis was made in 15 (29%) patients, 21% had another determined diagnosis while 50% remained of undetermined origin. Median CD4/CD8 ratio in CSF was 4.57 (IQR 3.39–5.47) in ocular sarcoidosis, 1.74 (1.60–3.18) in uveitis due to other determined cause ( P = .008), and 2.83 (2.34–3.54) in those with uveitis of undetermined origin ( P = .007). CD4/CD8 ratio >3.23 was associated with a diagnosis of ocular sarcoidosis. Conclusion : Determination of CD4/CD8 ratio in CSF can be useful for diagnosis work-up since a CD4/CD8 ratio >3.23 in CSF is associated with ocular sarcoidosis.